UV/VIS και FTIR φασματοσκοπική μελέτη της αλληλεπίδρασης του Artesunate με το DNA - Δημητρίου, Γεωργία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
The drug market is still dominated by small molecules, and more than 80% of the clinical development of drug candidates in the top 20 pharmaceutical firms is still based on small molecules. The high cost of developing and manufacturing “biological drugs” will contribute to leaving an open space for drugs based on cheap small molecules. At the border between bio-inspired design and rational design, one can imagine preparation of hybrid molecules with a dual mode of action to create efficient new drugs. Hybrid molecules are defined as chemical entities with two or more structural domains having different biological functions and dual activity, indicating that a hybrid molecule acts as two distinct pharmacophores. Artesunate is a water-soluble, semi-synthetic derivative of the sesquiterpine lactone artemisinin with antimalarial, antishistosomiasis, antiviral, and potential antineoplastic activities. Upon hydrolysis of artesunate's active endoperoxide bridge moiety by liberated heme in parasite-infected red blood cells, reactive oxygen species and carbon-centered radicals form, which have been shown to damage and kill parasitic organisms. Additionally, recent in vitro studies demonstrate that this agent induces DNA breakage in a dose-dependent manner. The objective of this study is to investigate and characterize the recently proposed mode of action of artesunate as anticancer agent. Ultraviolet/visible (UV/Vis) and Fourier transform Infrared (FTIR) spectroscopies are structure- and redox-sensitive tools able to monitor the non-bonding interactions between artesunate and DNA. Investigation of the drug-DNA interaction(s) is an essential part of drug designing, and also provides information about the drug’s mechanism of action at molecular level, since they lead to target (DNA) recognition and selectivity. The obtained UV/Vis and FTIR spectra are compatible with a series of definite non-bonding binding interactions between artesunate and DNA. These electrostatic interactions, are uncovered through the detected frequency upshift of the C6=O6 stretching mode of guanine, the frequency downshift of the C4=O4 stretching mode of thymine and the frequency downshift of the phosphate (PO2-) antisymmetric stretching mode. Infrared bands related to adenine and cytosine exhibit negligible changes and suggest no major interaction-binding of artesunate at these sites. In addition, significant transition from the B- to A-form of DNA is observed upon artesunate binding to DNA as evidenced by the appearance of the A-form marker band at 1189 cm-1, which is attributed to a sugar-phosphate backbone vibration. The combined results indicate that artesunate acts mainly as a major groove binder to B-form DNA, with some amount of external interaction with the negatively charged phosphate and sugar backbone. At higher drug:DNA ratios artesunate is capable of producing major B- to A-form transition of DNA. These results put the basis for further studies about the mechanism of action of artesunate as anticancer agent.
Keywords: Artesunate; Ultraviolet-Visible spectroscopy (UV/Vis); Infrared spectroscopy (FTIR, ATR); DNA; Φασματοσκοπία υπεριώδους – ορατού; Υπέρυθρη φασματοκοπία